Toll-like receptor 4 (TLR4) signaling in the trigeminal ganglion mediates facial mechanical and thermal hyperalgesia in rats - Araya, Erika Ivanna; Barroso, Amanda Ribeiro; Turnes, Joelle de Melo; Radulski, Débora Rasec; Jaganaught, Jovia-Roy Ashley; Zampronio, Aleksander Roberto; Chichorro, Juliana Geremias (Physiology & behavior, 2020)
•TLR4 antagonist improved hyperalgesia induced by LPS or mucosal incision.•It was identified an increase of phosphorylated NFκB in the TG in both pain models.•TLR4-NFκB pathway might be involved in pain development in inflammatory oral conditions. There is increasing evidence that the toll-like receptor 4 (TLR4) signaling pathway contribute to development of hyperalgesia in the trigeminal system. The aim of the present study was to investigate the role of TLR4 in the trigeminal ganglion (TG) in facial hyperalgesia induced by injection of Lipopolysaccharide (LPS) or intraoral mucosal incision, which is an orofacial postoperative pain model, in male Wistar rats. The TLR4 antagonist (LPS-RS, 20 µg/10 µL) was administrated 30 min before LPS injection into the TG (10 µg/10 µL) or oral mucosa (10 µg/50 µL). In the postoperative pain model, rats were treated with LPS-RS (20 µg/10 µL) into the TG for three consecutive days after the incision. Facial heat and mechanical hyperalgesia were assessed hourly after LPS injection or intraoral incision. In addition, expression of NFκB was assessed in the TG on day 3 after intraoral incision. Our results showed that blockade of TLR4 in the TG attenuated facial heat and mechanical hyperalgesia induced by LPS or by mucosal incision, and that both conditions are associated to increase of phosphorylated NFκB in the TG. In conclusion, the present study suggests that activation of TLR4-NFκB signaling pathway in the TG contributes to the development of facial heat and mechanical hyperalgesia and may contribute to pain in inflammatory oral conditions.